PENGARUH PENGGUNAAN ALAT PERMAINAN EDUKATIF TERHADAP PERILAKU MENCUCI TANGAN SISWA SEKOLAH DASAR NEGERI - Rismawan, Made -; Negara, IGNM Kusuma (Jurnal Riset Kesehatan Nasional, 2019)
ABSTRACT. Background. One of the causes of the low hand washing behavior in public elementary school students is due to the limited learning media used. The Educational Game Tool (EGT), specifically the snake ladder game, can be used as an alternative learning media about hand washing behavior in public elementary school students. This study aims to determine the effect of using EGT on hand washing behavior of public elementary school students in Denpasar City. Methods. This pre-experimental study used the design of the One Group Pre-Post Test Only and was carried out at SDN 3 Tonja. The sample in this study were 30 first grade students who were selected using a simple random sampling technique. The research instrument uses the Hand Washing Questioner and a snake ladder game developed by researchers. Result. The test results of data analysis using the Wilcoxon Sign Rank test showed that the handwashing behavior of all participants significantly increased after treatment (M = 15.5, p <0.001). Discussion. A pleasant EGT makes it easy for children to understand the positive behavior they want to instill. While carrying out this game, children begin to accept and be ready to carry out proper hand washing behavior in their daily lives. Through the games given, information about proper hand washing behavior is acceptable. Conclusion. EGT has an effect on increasing handwashing behavior in elementary school students.Keywords: educational game tool, hand washing behavior, elementary school students